Effect of selection on growth and carcass traits in Chemballi ducks - Behera, Rajalaxmi; Padhi, Mahendra Kumar; Kumar, Dhirendra; Naik, Prafulla Kumar; Swain, Bijaya Kumar; Sahu, Adhikari; Mishra, SK; Bhanja, Subrat Kumar (The Indian Journal of Animal Sciences, 2026)
The present study was conducted at Institute Duck Farm, Regional station, ICAR-Directorate of Poultry Research, Bhubaneswar, Odisha to evaluate the impact of individual selection applied for higher 8th week body weight on growth and carcass characteristics of Kuttanad Chemballi ducks. One thousand fertile eggs ofKuttanad-Chemballi ducks were procured from Government Duck farm, Kerala and were set at Institute hatchery for hatching. 637 ducklings were hatched (base S0 generation) and wing banded for individual recording of data. Individual selection was applied based on higher 8th week body weight in male ducks. Top 60 males and 140 females were used for regeneration of S1 and S2 generations and in each generation individual selection was applied on 8th week body weight. Body weight was recorded at bi-weekly intervals till 8th week followed by 4-week intervals till 20th week in each generation. Carcass characteristics were studied at 12 weeks of age in three generations. An improvement of 103.22 gram in 8th week body weight of male birds recorded in S2 generation over S0. The average daily gain was highest during 4th and 5thweek, and body weight declined in male ducks beyond 12-week age indicating that for a profitable enterprise, the male ducks should be sold by 12th week. A compensatory growth mechanism was observed in S1 generation where the reduced growth in early stages was compensated in later weeks of age. The study on carcass traits proved that there was improvement in the slaughter weight, edible carcass yield in S2 generation over S0 indicating the positive result of individual selection for body weight on carcass yield.